Contrast CT in Localization of Acute Lower Gastrointestinal Bleeding - Chwee Ming Lim; Iyer Shridhar; Lenny Tan; Wei-Keat Cheah (Asian Journal of Surgery, 2006)
Localization of the source of acute lower gastrointestinal bleeding is of paramount importance in its management as it allows for planned segmental resection rather than a “blind” abdominal total colectomy. Various methods of localization with radionuclide scan, mesenteric angiography and colonoscopy have been utilized, but none has been shown to be superior to others. The recent use of contrast-enhanced multislice computed tomography (MSCT) has generated much interest as it is rapid, noninvasive and readily accessible, and allows for excellent reformation on different planes. These are clear advantages in an emergency setting for accurate localization prior to surgery. We report a case where the use of MSCT resulted in prompt and accurate localization in a patient who presented acutely with massive lower gastrointestinal bleed. We believe that contrast-enhanced MSCT has the potential of accurately localizing the source of bleeding in an emergency setting, and should be part of the algorithm in the management of acute lower gastrointestinal bleeding.